Molecular architecture of the ribosome‐bound Hepatitis C Virus internal ribosomal entry site RNA. (24th November 2015) - Yamamoto, Hiroshi; Collier, Marianne; Loerke, Justus; Ismer, Jochen; Schmidt, Andrea; Hilal, Tarek; Sprink, Thiemo; Yamamoto, Kaori; Mielke, Thorsten; Bürger, Jörg; Shaikh, Tanvir R; Dabrowski, Marylena; et al.
Abstract: Internal ribosomal entry sites (IRESs) are structured cis ‐acting RNAs that drive an alternative, cap‐independent translation initiation pathway. They are used by many viruses to hijack the translational machinery of the host cell. IRESs facilitate translation initiation by recruiting and actively manipulating the eukaryotic ribosome using only a subset of canonical initiation factor and IRES transacting factors. Here we present cryo‐EM reconstructions of the ribosome 80S‐ and 40S‐bound Hepatitis C Virus (HCV) IRES. The presence of four subpopulations for the 80SHCV IRES complex reveals dynamic conformational modes of the complex. At a global resolution of 3.9 Å for the most stable complex, a derived atomic model reveals a complex fold of the IRES RNA and molecular details of its interaction with the ribosome. The comparison of obtained structures explains how a modular architecture facilitates mRNA loading and tRNA binding to the P‐site. This information provides the structural foundation for understanding the mechanism of HCV IRES RNA‐driven translation initiation. Synopsis: A 3.9‐Å cryo‐EM structure of the human ribosome bound to the HCV IRES reveals how this viral RNA element hijacks the translational machinery of the host cell to facilitate replication. The cryo‐EM structure of the mammalian ribosomal 80SHCV IRES complex has been solved at 3.9 Å. Large‐scale conformational changes such as inter‐subunit rotation and subunit rolling can be visualized. HCV IRES domain II is a highly dynamic element and promotes an open 40S subunit conformation by inducing a 40S head tilt via a wedge‐like mechanism. The structural basis for mRNA loading during HCV‐IRES‐driven internal initiation is provided. Abstract : A 3.9‐Å cryo‐EM structure of the human ribosome bound to the HCV IRES‐reveals how this viral RNA element hijacks the translational machinery of the host cell to facilitate replication.